Implementasi Metode Discovery Learning Dalam Pembelajaran Pendidikan Agama Islam SDN 89 Rejang Lebong - Mutiara Mahardika; Rana Meiyanda; Wahyu Asbabul Jannah; Sutarto; Aida Rahmi Nasution (Universitas Majalengka, 2026)
This study aims to analyze the implementation of the discovery learning method in Islamic Religious Education (PAI) learning at SDN 89 Rejang Lebong. The research employed a qualitative field research approach to obtain an in-depth understanding of the learning process carried out in the classroom. Data were collected through observation, interviews, and documentation involving Islamic Religious Education teachers and students as research subjects. The data were analyzed using the Miles and Huberman model, including data reduction, data display, and conclusion drawing. Data validity was ensured through source and technique triangulation. The results showed that the implementation of discovery learning was carried out systematically through planning, implementation, and evaluation stages. The application of this method succeeded in increasing students’ learning motivation, activeness, critical thinking skills, collaboration, and self-confidence during the learning process. Teachers acted as facilitators who guided students in discovering concepts independently through discussions, observations, and problem-solving activities. The findings indicate that discovery learning creates a more interactive, student-centered, and meaningful learning environment in Islamic Religious Education. This study contributes theoretically to strengthening constructivist learning theory and practically provides an alternative innovative learning strategy for improving the quality of Islamic Religious Education learning in elementary schools.